Access of primary and secondary literature by health personnel in an academic health center: implications for open access. - Maggio, Lauren A.; Steinberg, Ryan M.; Moorhead, Laura; O'Brien, Bridget; Willinsky, John (Journal of the Medical Library Association, 2013)
Purpose: The research sought to ascertain the types and quantity of research evidence accessed by health personnel through PubMed and UpToDate in a university medical center over the course of a year in order to better estimate the impact that increasing levels of open access to biomedical research can be expected to have on clinical practice in the years ahead. Methods: Web log data were gathered from the 5,042 health personnel working in the Stanford University Hospitals (SUH) during 2011. Data were analyzed for access to the primary literature (abstracts and full- text) through PubMed and UpToDate and to the secondary literature, represented by UpToDate (research summaries), to establish the frequency and nature of literature consulted. Results: In 2011, SUH health personnel accessed 81,851 primary literature articles and visited UpToDate 110,336 times. Almost a third of the articles (24,529) accessed were reviews. Twenty percent (16,187) of the articles viewed were published in 2011. Conclusion: When it is available, health personnel in a clinical care setting frequently access the primary literature. While further studies are needed, this preliminary finding speaks to the value of the National Institutes of Health public access policy and the need for medical librarians and educators to prepare health personnel for increasing public access to medical research.